2015
DOI: 10.2106/jbjs.n.01299
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatments of Tumor-Induced Osteomalacia Lesions in Long Bones

Abstract: Most lesions in long bones are located in the epiphysis, so curettage is first suggested to maintain joint function. If curettage is incomplete or there is a recurrence, secondary segmental resection should be considered curative. Changes of serum FGF-23 and phosphorus levels before and after the operation may be of prognostic help.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 38 publications
1
37
0
5
Order By: Relevance
“…Surgical treatment is recommended for patients with TIO in the bones, although there are several medical approaches [5][6][7]. If the tumor is not completely excised, patients with TIO cannot be cured [8,9]. Onethird of these tumors have been reported to occur in the bones, and the options for surgical treatment of tumors in the bones are tumor curettage and tumor segment resection [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical treatment is recommended for patients with TIO in the bones, although there are several medical approaches [5][6][7]. If the tumor is not completely excised, patients with TIO cannot be cured [8,9]. Onethird of these tumors have been reported to occur in the bones, and the options for surgical treatment of tumors in the bones are tumor curettage and tumor segment resection [7].…”
Section: Introductionmentioning
confidence: 99%
“…Onethird of these tumors have been reported to occur in the bones, and the options for surgical treatment of tumors in the bones are tumor curettage and tumor segment resection [7]. Previous studies have recommended segmental resection because tumor curettage was found to be associated with a high local recurrence rate [8,9]. Navigation-assisted surgery provides radiological information to guide the surgeon during surgery, and it has been reported to help safely resect malignant bone tumors, resulting in improved oncological and functional outcomes [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its rarity, few studies have focused on the surgical treatment strategy to achieve a better prognosis [4]. A tumor located on the long bone metaphysis, especially in unique areas such as the femoral head or tibial plateau, lack surgical guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [4] indicated that although segmental resection could ensure complete resection of the tumor, it would destroy the anatomic structure of the joint. To solve this problem, an artificial joint prosthesis or allogeneic bone segment should be followed to reconstruct the structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation